The effects of coronavirus on global energy prices - İncekara, Rahmi (My University, 2020)
Abstract:It appears that the impact of the crisis caused by the coronavirus (Covid-19) epidemic in theworld is experienced in many different areas, especially in health. The drastic falls in oil pricesindicate that energy is also one of those areas. Oil prices were the first to suffer from this lack ofdemand, as measures taken to prevent the spread of the epidemic slowed the economy, severelyreducing demand for energy. Then there were also falls in the prices of natural gas and otherenergy sources. In terms of the impact of the epidemic on the energy sector, it is seen that theeconomic crisis experienced in energy importer countries is directly reflected in energy exportingcountries. Even though decreasing energy prices, especially oil, firstly was a very positivedevelopment for energy-importing countries, the problems of the exporting countries in theframework of the global economic cycle will affect them eventually. The success of energyexporting countries in their struggle with the crisis will determine the degree of dependence onthe exports of these energy products. Especially for countries whose share of energy exports inrevenue budgets are very high and foreign exchange reserves are low, the low level of oil and gasprices for a long time can have serious economic and political consequences. In this study, theeffects of coronavirus on energy prices, the effects of countries on energy prices, the course ofchanges in energy prices and future scenarios are examined.